IN THE OCEAN - Druzhininskaya, Anastasia (New York, NY : Clever Publishing, 2022)
Dive deep below ocean and sea waters in this brand-new addition to Clever's bestselling Look & Find series! Discover a whole new world and more in this interactive book with 800 ocean-themed objects like dolphins, sharks, fish, whales, coral, and so much more! Jam-packed with colourful illustrations, In the Ocean provides endless entertainment for curious toddlers and their families. With 800 objects to discover inside, this special oceans-themed Look & Find includes engaging questions and prompts on each page. An educational and entertaining experience, children will develop their attention skills while counting, learning, and discovering.
"More than 800 things to find!" --Cover
Keywords: Picture puzzles -- Juvenile literature; Ocean -- Juvenile literature; Picture books; Picture puzzles